Guselkumab demonstrates long-term efficacy and maintenance of treatment response postwithdrawal in systemic treatment-naïve patients and nonresponders to fumaric acid esters: results from parts II and III of a randomized active-comparator-controlled phase IIIb trial (POLARIS) - Thaçi, Diamant; Pinter, Andreas; Sebastian, Michael; Termeer, Christian; Sticherling, Michael; Gerdes, Sascha; Schäkel, Knut; Wegner, Sven; Krampe, Stefanie; Bartz, Holger; Rausch, Christian; Taut, Friedemann; et al. (British journal of dermatology, 2024)
The anti-interleukin-23 antibody guselkumab (GUS) demonstrated favourable week 24 efficacy and safety over fumaric acid esters (FAE) in systemic treatment-naïve patients with moderate-to-severe plaque psoriasis (study part I).To compare, in study part II, the sustainability of treatment responses (weeks 24-32) in GUS- and FAE-treated patients and treatment responses (weeks 32-56) in patients treated with GUS and FAE and in FAE nonresponders switching to GUS; and, in part III, to investigate the maintenance of response through week 100 in patients withdrawn from GUS at week 56.At week 0, systemic treatment-naïve patients were randomized 1 : 1 to GUS or FAE as per label. At week 32, patients with a Psoriasis Area and Severity Index (PASI) 75 (≥ 75% improvement in PASI score) response (r) continued assigned treatment (GUSr-GUS; FAEr-FAE), whereas nonresponders (nr) received GUS (FAEnr-GUS; GUSnr-GUS). GUS-treated patients with a week 56 PASI 90 response (≥ 90% improvement in PASI score) were withdrawn (w) and followed until loss of response or week 100.At week 32, 98% (n = 54/55) of GUS- and 41% (n = 14/34) of FAE-treated patients were PASI 75 responders. At week 56, 91%, 50% and 80% of GUSr-GUS, FAEr-FAE and FAEnr-GUS patients, respectively, achieved a PASI 90 response; 72%, 29% and 45%, respectively, achieved a Dermatology Life Quality Index score of 0/1. At week 100, 44 weeks postwithdrawal, 47% (n = 17/36) and 25% (n = 3/12) of GUS-GUSw and FAEGUSw patients, respectively, maintained a PASI score ≤ 5. Overall, the adverse event and discontinuation rates were lower for GUS than FAE.In these exploratory analyses, GUS, as a first-line systemic treatment or second-line systemic treatment in FAE nonresponders, was associated with long-term clinical efficacy up to week 100, including a withdrawal period.
Veröffentlicht: 22. Dezember 2023
Gesehen am 29.11.2024